Micro-grid voltage control strategies considering uncertain PV generation with analysis method. Issue 6 (February 2019) - Hu, Defeng; Cheng, Ke; Guo, Jincheng; Wang, Qian
Abstract: PV is one of intermittent renewable sources, which are complicated to forecast its influence on the voltage of micro-grid system. The strategies of maintaining voltage stability of micro-grid with uncertain PV are studied in this paper. Randomize values based on real PV output and loads are used. The effects of both quantity and content of traditional or new micro-grid device on voltage stability are analysed. Other factors which can improve the performance like various algorithms and parameters are discussed in this paper. Energy saving issue is also included in the paper.